SUBSTITUSI TEPUNG TEMPE JAGUNG PADA PEMBUATAN MIE BASAH [Substitution of Corn Tempe Flour on Wet Noodle] - Sri Setyani; Sussi Astuti; Florentina Florentina (Jurnal Teknologi & Industri Hasil Pertanian, 2017)
The purpose of this research was to find the best formulation of corn tempe flour and wheat flour to produce chemically, physicochemically and organoleptically acceptable sweet noodle. The formulation consisted of 4 levels ratio of 100% corn tempe flour and wheat flour L1 (10:90), L2 (20:80), L3 (30:70), L4 (40:60) w/w with 6 replications. The experiment was arranged in Complete Randomized Block Design (CRBD). Data were analyzed by using analysis of variance, further were tested by using the Least Significant Difference (LSD) test in 5% level of significance. The result showed that the best formula was L3 treatment (30% corn tempe flour  and 70% wheat flour). The characteristic  of this noodle were 23.31% moisture content, 1.55% ash, 8.50% fat,   9.11% protein, 57,2% carbohydrate, 9.85% cooking loss, and 13.50 %water absorption. The wet noodle score sensory of texture was 2,88 (rather chewy), taste’s and aroma score was 3.05 (typical corn), and the overall of acceptance was  2.93 (like).Keywords: chemical-physicochemical and organoleptic characteristics, corn tempe flour,  wet noodle,wheat.